Il dibattito su valutazione ed evidenze: per un processo valutativo credibile e trasparente - Maria Lucia Giovannini (LED Edizioni Universitarie, 2014)
The Debate on Evaluation and Evidence: For a Credible and Transparent Evaluation Process This paper presents the main issues concerning the lively national and international debate on the evidence in the evaluation process, with specific attention to the American context in which the debate is particularly prominent. Initial consideration is given to the fundamental steps and elements of reflection and debate associated with the theme of evidence-based education in its broadest sense. Then, the specificity of evidence in relation to research and decision making processes is examined. Particular attention is given to key aspects relating to the development of a theory to describe the role of evidence in evaluation that takes account of its multifaceted nature, the implied value attributed to it, the context in which it is acquired and used, the judgement process that attributes it value and the use of value judgments in the decision-making process. Finally, some issues which make the debate on this theme also relevant to the Italian context are presented in order to assure that the provision or acquisition of evidence is supportive of an evaluation process that is both credible and transparent.